Warranty and Preventive Maintenance for Remanufactured Products : Modeling and Analysis - Alqahtani, Ammar Y.; Gupta, Surendra M.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
The exponential increase in the development of technology coupled with the customers' immense desire to possess the newest technological products makes for truncated product lifespans, which instigates a substantial upsurge in their rate of disposal. Attempts have been made to establish specialized product recovery facilities with the intention of diminishing the volume of accumulated waste delivered to landfills using product recovery procedure such as remanufacturing. The economic benefits produced by remanufacturing also portray the role of product recovery in a more attractive light. The quality of a remanufactured product is uncertain for some consumers. Therefore, these consumers possess insecurities in deciding whether or not the remanufactured products will render the same expected performance. This ambiguity regarding a remanufactured product could possibly result in the consumer deciding against its purchase. With such consumer apprehension, remanufacturers often seek market mechanisms that provide reassurance as to the stable durability that these products still maintain. One strategy that the remanufacturers often use is the utilization of the premise of offering product warranties with preventive maintenance on their products. This book is concerned with the practice and theory of warranty management and preventive maintenance, particularly in relation to remanufactured products' warranties. Models developed in this book can be used for making the right decisions in offering renewable, nonrenewable, one and two dimensional warranty policies, and for managerial decision in considering maintenance contracts or outsourcing maintenance for remanufactured components and products. Features Discusses a variety of warranty policies and preventive maintenance of remanufactured products (first book to do so) Presents mathematical models and applications for warranty policies using examples and simulation results Considers cost and optimization problems from the remanufacturer's and buyer's points of views Provides a foundation for academicians interested in building models in the area of warranty and preventive maintenance analysis of remanufactured products Offers the essential methodology needed by practitioners involved with warranty and preventive maintenance analysis, along with extensive references for further research.
Chapter 1 Introduction and Overview. Chapter 2 Review of Product Recovery, Sensor-Embedded Products, Warranty and Maintainability. Chapter 3 Product Warranty and Preventive Maintenance. Chapter 4 Warranty Policies for Remanufactured Products with Preventive Maintenance Strategy. Chapter 5 Modelling Warranty Costs with Preventive Maintenance for Remanufactured Products. Chapter 6 Representative Remanufacturing Facility used for the Analysis of Warranty and Preventive Maintenance. Chapter 7 Cost Analysis of Simple Non-Renewing Warranties Group 1. Chapter 8 Cost Analysis of Simple Non-Renewing Warranties Group 2. Chapter 9 Cost Analysis of Combination Warranties. Chapter 10 Cost Analysis of Renewing Warranties. Chapter 11 Cost Analysis of Two-Dimensional Warranties. Chapter 12 Conclusions.
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Operations Research; Cost Analysis; Cost Sharing; Environmentally Conscious Manufacturing; Free Replacement; Modelling Failures; Renewable; Remanufacturing -- Reliability; Recycled products -- Reliability; Recycled products -- Maintenance and repair; Warranty; Electronic books